Pengaruh Kinerja Makroekonomi Terhadap Dana Pihak Ketiga Perbankan Syariah Indonesia - Inti Selvia; Putri Apria Ningsih; Aztyara Ismadharliani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to find out empirical evidence about the effect of inflation, exchange rates and interest rates on third party funds. The independent variables in the research are inflation, exchange rates and interest rates. The type of research used is quantitative. Quantitative research. The objects in this study are all BUS (Sharia Commercial Banks) whose data is listed on the Financial Services Authority (OJK) website in 2018-2021. Sources of data in this study are: Secondary data. Where secondary data is data obtained from a second source or secondary source of the data we need. Secondary data sources obtained through the OJK, BPS and BI websites from 2018-2021. The sampling method in this study is the number of companies that were sampled in this study were 15 companies. The data used in this study is secondary data in the form of financial reports. Statistical methods using multiple linear regression analysis, t test, f test and analysis of the coefficient of determination. The results of this study indicate that the inflation variable t test (X1) has an effect on Third Party Funds. The Exchange Rate Variable (X2) has an effect on third party funds. Interest Rate Variable (X3) has no effect on third party funds. This study test F (simultaneous test) Inflation (X1), Exchange Rates (X2) and Interest Rates (X3) Obtain the result that the Independent variInflation, Exchange Rates, Interest Rates and Third Party Funds.able has a simultaneous (simultaneous) influence on Third Party Funds, namely 0.000 <0 ,05.